Security Problems of Chaotic Image Encryption Algorithms Based on Cryptanalysis Driven Design Technique - Muhammad, Zahir Muhammed Ziad; Ozkaynak, Fatih (Ieee-Inst Electrical Electronics Engineers Inc, 2019)
Robust protocols are needed to create a secure computing system. Protocols designed without considering various design criteria result in many vulnerabilities. Security has many aspects. The slightest defect in the design processes affects the whole system security. Chaos based image encryption algorithms have become increasingly popular in the recent period. However, most of these algorithms are often based on cryptanalysis driven design technique. Therefore, the security of these algorithms is doubtful as long as the threat of attack continues. In this paper, attention has been drawn to this problem. First, the security problems of two different chaos based image encryption algorithms have been analyzed. In the second analyzed study, the security problem of the first analyzed study has been examined and a new improved version has been published. The common point of these two analyzed studies is that both the original and the improved algorithm are designed on the basis of the cryptanalysis has driven design approach. In otherwords, the security of these two algorithms is still doubtful. In this study, security problems have been shown for both algorithms and the encryption algorithms have been broken. In the second part of the study, a road map based on a provable secure driven design approach is presented for future studies to avoid such problems.
Keywords: Chaos; cryptography; cryptanalysis; image encryption; security problem